ТОТАЛИТАРИЗМЫН СУДАЛГААНД ЭРДЭМТДЭЭС БАРИМТАЛСАН АРГА ЗҮЙН ХАНДЛАГУУДЫН ТУХАЙД - Ж.Жаргал (Politology, 2023)
The purpose set by the author of the article is to review theory and methodology used by western scholars to study totalitarianism. The problem of the totalitarianism is difficult. Scholars from the different countries had a different views about the totalitarianism. Also they have a diverse theory and methodology. We can classify them like this: political, constitutional law, political systems theory, modernizational, social and political psychology, socio-cultural and political anthropology. They all have advantages and weaknesses but they restore one another, allowing us to learn more about totalitarianism